Advances in orchid conservation: biotechnology applications and global trade dynamics - Sarmah, Dipika; Gurung, Natasha; Saini, Pawan; Devi, Mayengbam Premi; Mohapatra, Priyadarshani; Pramanik, Kartik; Jena, Chinmaya; B., Raghupathi (Frontiers in Conservation Science, 2025)
Orchids are one of the most diverse and economically significant plant families, recognized for their ornamental, medicinal, and commercial value in global floriculture. However, the conservation of orchid species faces significant challenges due to habitat destruction, illegal trade, and climate change. In situ and ex situ conservation approaches, including advanced micropropagation technologies, have been pivotal in preserving the genetic diversity of endangered orchids. Cutting-edge modern biotechnological techniques including in vitro propagation, cryopreservation, and seed banking and its integration can be promising in the conservation of orchids. Furthermore, international policies such as Convention on International Trade in Endangered Species of Wild Fauna and Flora have been enacted to regulate the trade of orchids, though illegal harvesting persists. This paper offers a comprehensive overview of both conservation strategies and the commercial aspects of orchids, emphasizing the need for balanced trade and sustainable conservation practices.